2021
DOI: 10.1021/acsnano.1c07319
|View full text |Cite
|
Sign up to set email alerts
|

Polysorbate- and DNA-Mediated Synthesis and Strong, Stable, and Tunable Near-Infrared Photoluminescence of Plasmonic Long-Body Nanosnowmen

Abstract: Direct photoluminescence (PL) from metal nanoparticles (NPs) without chemical dyes is promising for sensing and imaging applications since this offers a highly tunable platform for controlling and enhancing the signals in various conditions and does not suffer from photobleaching or photoblinking. It is, however, difficult to synthesize metal NPs with a high quantum yield (QY), particularly in the near-infrared (NIR) region where deep penetration and reduced light scattering are advantageous for bioimaging. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…The polymer template is utilized to confine AgNSs inside the polymer layer, improving the structural stability of the AgNAs and minimizing material cytotoxicity. [ 40–42 ] Our results indicated that interparticle proximity between adjacent AgNSs in AgNAs can control absorption responses at NIR wavelengths, regulating PA signal generation. We also showed that AgNAs exhibited higher PA signals than counterpart AuNAs by promoting heat transfer into the local environment.…”
Section: Introductionmentioning
confidence: 84%
“…The polymer template is utilized to confine AgNSs inside the polymer layer, improving the structural stability of the AgNAs and minimizing material cytotoxicity. [ 40–42 ] Our results indicated that interparticle proximity between adjacent AgNSs in AgNAs can control absorption responses at NIR wavelengths, regulating PA signal generation. We also showed that AgNAs exhibited higher PA signals than counterpart AuNAs by promoting heat transfer into the local environment.…”
Section: Introductionmentioning
confidence: 84%
“…It is very important to choose an appropriate capping agent in the shape-controlled synthesis of Au–Cu Janus nanostructures. The alkylamines and DNA can selectively bind to Cu, which helps Cu growth on the surface of the Au nanostructure ( Liu and Fichthorn, 2017 ; Kim et al, 2021 ). For example, Zhang and coworkers proposed a general seed-mediated growth method for the synthesis of Au–Cu Janus nanostructures by HAD and CTAB as surfactants ( Jia et al, 2021 ).…”
Section: Synthesis Of Au–cu Nanostructuresmentioning
confidence: 99%
“…Currently, the rational design and controlled synthesis of bimetallic heterostructures have attracted great interest due to their fantastic properties and wide applications in catalysis, optics, and magnetism related fields. Compared to heterostructures in the core–shell configuration, Janus structures are highly desired owing to their extensive applications in self-assembly, catalysis, sensing, and biological fields. Especially, the enhanced charge separation and synergistic effect due to the physical separation of the composed materials in Janus structures led to significant improvement in synergistic catalysis. …”
Section: Introductionmentioning
confidence: 99%